Challenges and possible solutions in cross-disciplinary and cross-sectorial research teams within the domain of e-mental health. Issue 4 (1st September 2021) - Nordgreen, Tine; Rabbi, Fazle; Torresen, Jim; Skar, Yngvar Sigmund; Guribye, Frode; Inal, Yavuz; Flobakk, Eivind; Wake, Jo Dugstad; Mukhiya, Suresh Kumar; Aminifar, Amin; Myklebost, Sunniva; Lundervold, Astri J.; et al.
Abstract : Purpose: Mental illness presents a huge individual, societal and economic challenges, currently accounting for 20% of the worldwide burden of disease. There is a gap between the need for and access to services. Digital technology has been proven effective in e-mental health for preventing and treating mental health problems. However, there is a need for cross-disciplinary efforts to increase the impact of e-mental health services. This paper aims to report key challenges and possible solutions for cross-disciplinary and cross-sectorial research teams within the domain of e-mental health. Design/methodology/approach: The key challenges and possible solutions will be discussed in light of the literature on effective cross-disciplinary research teams. Findings: Six topics have been key challenges in our cross-disciplinary and cross-sectorial research team: to develop a shared understanding of the domain; to establish a common understanding of key concepts among the project participants; to involve the end-users in the research and development process; to collaborate across sectors; to ensure privacy and security of health data; and to obtain the right timing of activities according to project dependencies. Research limitations/implications: This study focuses to increase knowledge and training in cross-disciplinary and cross-sectorial research, as this is often referred to as an important tool when developing sustainable solutions for major societal challenges. Practical implications: This study needs to include theory and skills training in cross-disciplinary research in research training. Social implications: Cross-disciplinary teams have the potential to address major societal challenges, including more perspectives and more stakeholders than single disciplinary research teams. Originality/value: Major societal challenges require complex and sustainable solutions. However, there is a lack of knowledge about how cross-disciplinary and cross-sectorial research teams may work productively to solve these challenges. This paper shares experiences regarding the challenges and possible solutions for productive collaboration in cross-disciplinary and cross-sectorial research teams within the domain of e-mental health services.